Pomembni dokumenti v zdravstveni negi otroka - Zorec, Jelka (Obzornik zdravstvene nege, 2001)
One of basic tasks of nurses engaged in nursing care of children is a thoroughknowledge of rules and regulations affecting their professional activities. Also children and their parents should be informed about basic documents of the rights of children. The article lists some laws, regulations,articles, conventions and codices, rights and duties; the familiarity with which brings satisfaction for involved in the process of nursing care.
Keywords: Child; Child advocacy; dokumenti; Ethics, nursing; informacije; otroci; Parents; Pediatric nursing; pediatrija; zdravstvena nega; zdravstvena politika